Jet microchannel with sawtooth wall for efficient cooling of high-power electronics. (1st June 2023) - Wu, Zhihu; Jiang, Zhiyao; Yan, Wujuan; Yang, Yuchi; Kang, Jin; Zheng, Kai; Bu, Weihai; Wang, Wei; Song, Bai
Highlights: An embedded heat sink featuring jet microchannel with sawtooth wall is presented. The sawtooth walls simultaneously reduce the thermal resistance and pressure drop. For mm-sized chips with heat fluxes around 1000 W cm −2, the COP can reach 20000. Over 2100 W cm −2 of heat can be dissipated with a pumping power of 1.26 W cm −2 . Abstract: Dissipation of ultrahigh heat fluxes is critical to modern electronic chips as they become ever more compact and powerful. Here, by employing a systematic numerical study, we present a highly-efficient embedded single-phase water-cooled silicon heat sink featuring a manifold with interdigitated inlets and outlets and jet microchannels with sawtooth side walls. Compared to straight channels, the sawtooth walls reduce blockage of the jet inflow and therefore the pressure drop. Meanwhile, the sawtooth profile helps suppress the large recirculation region around the jet inlet and generate small vortices near the channel walls which facilitate fluid mixing and enhance heat exchange. This simultaneous enhancement of heat transfer and reduction of pressure drop leads to some of the highest cooling efficiencies. In particular, for a 3 × 3 mm 2 chip at a temperature rise of 60 K, dissipation of heat fluxes over 2100 W cm −2 is possible with a pumping power of about 1.3 W cm −2 . For heat fluxes around 1000 W cm −2, the coefficient of performance can reach beyond 20, 000. In addition to the high performance, our heat sink can in principle be manufactured via standard silicon microfabrication technology.